-6x-6=-18

Simple and best practice solution for -6x-6=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-6=-18 equation:


-6x-6=-18

We simplify the equation to the form, which is simple to understand
-6x-6=-18

We move all terms containing x to the left and all other terms to the right.
-6x=-18+6

We simplify left and right side of the equation.
-6x=-12

We divide both sides of the equation by -6 to get x.
x=2

See similar equations:

| 7-4(3m+2-3)-4=17 | | 2+7(3-4k)=31 | | 5m^2+m/7m | | 4(v+5)=-8 | | 7b(-6b-4)= | | 3d+16=d+18 | | 4/x-1/2x=-7/4 | | -4/7(x1/4)=3/7 | | 38=20+3p | | 4/b-1/2b=-7/4 | | a+5=19 | | -68+-17= | | 3/5q-7/5=2q | | 2.4x+5.6=11.2 | | 7-5y=34 | | 14m+26=0 | | 0=14m+26 | | Y=3(3y-1)-13 | | 26+8= | | (4+3i)/(5-2i) | | 3.4d-1.7=6.8 | | 3z+6z=60-1z | | 4+3i/5-2i | | 40p+7(1.5)p=489.85 | | 4p^2+4p-48=0 | | 6(4b-5)=23 | | (4w+3)(8+w)=0 | | 2(4t-2)+t=16t | | ((2/x)+3)=((5x-7)/x) | | 6(y-1)+5y-6=65 | | X^2+9x+6/(x+6) | | x^2+(7/2)x-2 |

Equations solver categories